Measuring Intergroup Ideologies: Positive and Negative Aspects of Emphasizing Versus Looking Beyond Group Differences. (December 2015) - Hahn, Adam; Banchefsky, Sarah; Park, Bernadette; Judd, Charles M.
Research on interethnic relations has focused on two ideologies, asking whether it is best to de-emphasize social-category differences (colorblind) or emphasize and celebrate differences (multicultural). We argue each of these can manifest with negative outgroup evaluations: Assimilationism demands that subordinate groups adopt dominant group norms to minimize group distinctions; segregationism holds that groups should occupy separate spheres. Parallel versions can be identified for intergender relations. Scales to measure all four ideologies are developed both for ethnicity (Studies 1 and 2) and gender (Studies 3 and 4). Results demonstrate that the ideologies can be reliably measured, that the hypothesized four-factor models are superior to alternative models with fewer factors, and that the ideologies relate as predicted to the importance ascribed to group distinctions, subordinate group evaluations, and solution preferences for intergroup conflict scenarios. We argue that this fourfold model can help clarify theory and measurement, allowing a more nuanced assessment of ideological attitudes.